(untitled) (Journal of the Bangladesh Agricultural University, 2024)
Climate change poses significant challenges all over the world. Developing countries whose economic sector profoundly depends on agriculture are especially vulnerable to climate change. To face climate change impacts, adaptation is found to be one of the most important options. In the case of adaptation to climate change in the agricultural sector, extension service is a crucial actor. Therefore, this study explores the different roles agricultural extension services play in developing countries in climate change adaptation. This article follows a systematic literature review through the process of Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The present study considered only peer Scopus-indexed journals published between 1996 and May 2024. Total (n=113) research articles are found initially based on the nature of the study and keywords. Total (n=68) articles were excluded primarily based on published language, Scopus-indexed research article, repeated article, geographical location, climate change adaptation, and role of extension service as a key focus of the study. Finally, (n=45) papers were taken for analysis. The synthesized result suggests that extension services mainly perform the following roles in climate change adaptation: i) raising awareness of climate change, ii) innovation dissemination, iii) information management, iv) production management, v) implementing policies and programs, vi) capacity development, vii) supply of input, and viii) liaison with existing climate change actors. Additional research should evaluate extension agents’ barriers to achieving successful outcomes and their capacity-building needs in developing countries vulnerable to climate change. J Bangladesh Agril Univ 22(4): 490–496, 2024